Realizing Simultaneous X‐Ray Imaging and Dosimetry Using Phosphor‐Based Detectors with High Memory Stability and Convenient Readout Process. (18th May 2022) - Yang, Zetian; Hu, Jieqi; Van der Heggen, David; Feng, Ang; Hu, Hairong; Vrielinck, Henk; Smet, Philippe F.; Poelman, Dirk
Abstract: Flexible X‐ray storage phosphor sheets are regarded as promising alternatives to conventional electronic flat‐panel X‐ray detectors, enabling X‐ray imaging and dosimetry in less accessible situations. However, it is a challenge to develop phosphor‐based detectors with high memory stability and convenient readout processes. Here, an approach to realize this using radiation‐induced photoluminescence tuning in (Ba1‐ x Sr x )2 SiO4 :Eu phosphors is demonstrated, ascribed to the reduction of Eu 3+ toward Eu 2+ . The associated photoluminescence spectral change and the accompanying color contrast in response to the radiation dose are exploited for simultaneous X‐ray dosimetry and imaging. The recorded image can be read out conveniently by a regular photo camera upon UV illumination and the radiation dose can be extracted during the imaging process in a ratiometric way via the green to red pixel intensity, avoiding the need for absolute intensity measurement. Moreover, the imaged information can be maintained for longer than 28 days and the plate can be reused for X‐ray detection after bleaching upon 420 nm illumination, exhibiting superior memory retention ability and good cycling resistance. These results reveal the great potential of (Ba1‐ x Sr x )2 SiO4 :Eu for X‐ray‐based microbeam radiation therapy and nondestructive inspection and are expected to stimulate research on phosphor‐based photoluminescence modulated detectors. Abstract : This study presents an approach to develop phosphor‐based X‐ray detectors with high memory stability and convenient readout processes using radiation‐induced photoluminescence tuning in (Ba1‐ x Sr x )2 SiO4 :Eu phosphors. The associated photoluminescence change and the accompanying color contrast in response to the radiation dose are exploited for simultaneous X‐ray imaging and dosimetry, showing great potential for a large dose range or high dose rate radiography.